Crack closure and initiation stresses of coal subjected to thermo-gas-mechanical coupling - Gao Yanan (Thermal Science, 2017)
In this paper, the orthogonal experiment method is employed to design physical tests of coal under different temperatures, confining pressures, and gas pressures. The crack closure stress and crack initiation stress are calculated using four known methods, i. e. axial strain method, axial stiffness method, crack volume method, and strain response method. The obtained results are compared, and the advantages and drawbacks for the used methods are also discussed. The influences of the three factors on the crack closure and crack initiation stresses are analyzed.